Magnolol as a potent antifungal agent inhibits Candida albicans virulence factors via the PKC and Cek1 MAPK signaling pathways - Xie, Yufei; Hua, Hong; Zhou, Peiru (Frontiers in Cellular and Infection Microbiology, 2022)
Magnolol, a lignin compound extracted from Magnolia officinalis Cortex, has been found to have prominent antifungal effects against Candida albicans. However, the specific mechanism still remains unclear. Therefore, this study aimed to further explore the inhibition mechanism of magnolol against Candida albicans virulence factors and the related signaling pathways. By an XTT reduction assay, a hyphal formation assay, confocal laser scanning microscopy, transmission electron microscopy, a calcofluor white staining assay, and a cell wall β-glucan quantitative detection assay, we evaluated the inhibitory effects of magnolol against the adhesion, hyphal formation, biofilm viability, biofilm spatial structure, and cell wall ultrastructure of Candida albicans. Moreover, by RNA sequencing and qRT-PCR, we confirmed the effects of magnolol in inhibiting the gene expression of Candida albicans virulence factors and the related signaling pathways. The results revealed that the adhesion and hyphal formation of Candida albicans were inhibited significantly by magnolol. The viability and spatial structures of Candida albicans biofilms were further weakened. Candida albicans ultrastructure showed partial thinning of cell walls and even rupture, with cytoplasmic leakage. The cell wall intergrity and β-glucan content were also radically reduced. Moreover, magnolol caused significant inhibition of the expression of Candida albicans adhesion, invasion, hyphal formation, biofilm formation, β-1,3-glucan synthesis, and hydrolase secretion-related genes, including ALS1, ALS3, EFG1, EAP1, FKS1, FKS2, PLB2, and SAP2. Furthermore, the PKC pathway-related genes (RHO1, PKC1, BCK1, MKK2, MKC1) and Cek1 pathway-related genes (CDC42, CST20, STE11, HST7, CEK1) were also significantly downregulated, indicating that the inhibition of magnolol against Candida albicans virulence factors might be related to PKC and Cek1 MAPK signaling pathways. In conclusion, the findings of this study confirmed the inhibition mechanism of magnolol against Candida albicans virulence factors, which might be related to PKC and Cek1 MAPK pathways, thus laying the theoretical foundation for its clinical antifungal applications.